2005
DOI: 10.1101/gad.1302205
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of the human TREX complex to mRNA during splicing

Abstract: In yeast, the TREX complex contains the THO transcription elongation complex, which functions in direct cotranscriptional recruitment of the mRNA export proteins Sub2 and Yra1 to nascent transcripts. Here we report the identification of the human THO complex and show that it associates with spliced mRNA, but not with unspliced pre-mRNA in vitro. Transcription is not required for this recruitment. We also show that the human THO complex colocalizes with splicing factors in nuclear speckle domains in vivo. Consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
503
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(557 citation statements)
references
References 35 publications
37
503
1
2
Order By: Relevance
“…The gH and gL genes of RRV, like most other RRV genes, do not have introns that are spliced out during mRNA processing. It has been shown that TREX and the exon-junction complex (EJC) binds onto mRNA in a splicing-dependent manner to facilitate the efficient nuclear export of spliced mRNAs in eukaryotic cells (19,23,31). We asked whether the lack of appropriate ribonucleoprotein (RNP), due to a lack of splicing, was responsible for the poor expression of gH and gL mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…The gH and gL genes of RRV, like most other RRV genes, do not have introns that are spliced out during mRNA processing. It has been shown that TREX and the exon-junction complex (EJC) binds onto mRNA in a splicing-dependent manner to facilitate the efficient nuclear export of spliced mRNAs in eukaryotic cells (19,23,31). We asked whether the lack of appropriate ribonucleoprotein (RNP), due to a lack of splicing, was responsible for the poor expression of gH and gL mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…In mammals, the TREX complex is recruited primarily to the 5 0 end of transcripts through cooperative action of the nuclear cap-binding complex and the spliceosome [16,17]. Once bound to the mRNA, the TREX complex promotes nuclear export of fully processed transcripts through the nuclear pore by direct interactions between the TREX component, Aly, and the nuclear export factor, TAP-p15 [18,19].…”
Section: Splicing Directs Mrnp Formationmentioning
confidence: 99%
“…Whereas genes with regulatory functions are enriched for 5UIs, genes encoding proteins targeted to the endoplasmic reticulum (ER) or mitochondria are significantly depleted of such introns [3,24]. When 5UIs are present, they are necessarily the most 5 0 proximal introns in a transcript, and 5 0 proximal introns have a disproportionate role in regulating transcription, mRNA export, and translation [16,[25][26][27][28]. However, 5 0 proximity alone cannot explain the functional distribution of transcripts that do or do not contain 5UIs.…”
Section: Splicing Directs Mrnp Formationmentioning
confidence: 99%
“…On the other hand, in agreement with data obtained from morphological experiments (Figure 3), in FMIP knockdown cells, C/EBPalpha is expressed even in the presence of muscle differentiation medium (Figure 4c), suggesting that FMIP downmodulates polyadenylated C/EBPalpha mRNA expression under these conditions. C/EBPalpha counteracts the effect of FMIP on adipocyte/myocyte differentiation Recently, a mammalian homologue of THOC5 in Drosophila melanogaster which is a member of the nuclear export complex (Rehwinkel et al, 2004), was identified as fSAP79 (Masuda et al, 2005). The aminoacid sequence of fSAP79 is identical to FMIP.…”
Section: Fmip Influences the Expression Of C/ebpalpha Gene During Adimentioning
confidence: 99%